Fitness of Cassiopea polyps Inoculated with Different Types of Symbionts - Mu'alimah Hudatwi; Diah permata Wijayanti; Ambariyanto Ambariyanto; Michio Hidaka (Marine Science Department Diponegoro University, 2022)
The specificity of the relationship between cnidarian hosts and symbiotic dinoflagellates (zooxanthellae) differs among host species. Some cnidarian hosts can establish symbiotic relationship with various types of zooxanthellae, while others exhibit high fidelity to specific symbiont type. It is not known how compatibility or specificity of the relationship is determined. We hypothesized that some cnidarian hosts select symbiont type that leads to highest fitness when the host is flexible with symbiont type and more than one types of symbionts are available. As a first step to study this possibility, compatibility of clonal polyps of Cassiopea sp. with six strains of cultured zooxanthellae and the fitness of the host associated with different types of symbionts were studied. Polyp diameter was measured and the number of asexual buds were calculated as a measure of host fitness. The number of zooxanthellae in host and in asexual buds was also measured as a measure of symbiont fitness. Three strains KB8 (clade A), Y106 (clade A), and K100 (clade B) were compatible with the Cassiopea polyps, while other three strains, Y103 (clade C), K111 (clade D), and K102 (clade F) were incompatible. No clear difference in the fitness was found among the polyps inoculated with compatible and incompatible symbiont strains. In one experiment, a compatible strain Y106 seemed to decrease host fitness, but this should be checked by further studies. This study suggests that feeding regimes and long observation period might be important when fitness of hosts associated with different types of symbionts is investigated.